PENGELOLAAN PEMBIYAAN PENDIDIKAN DI SEKOLAH TINGGI ILMU AL-QUR’AN AS-SYIFA - Hidayat, Ara; Anshorudin, Rizal; Rahman Hakim, Arif; Irfan, Muhammad (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research discusses the management of educational financing at the (STIQ) As-Syifa, a Private Islamic Higher Education Institution (PTKIS) under the auspices of the Yayasan As-Syifa Al-Khoiriyyah. The main focus of the research is on financial management, which includes planning, organizing, implementing, and supervising educational funds. A qualitative approach was used to analyze data obtained through interviews, observations, and documentation. The results of the study indicate that the financial management at STIQ As-Syifa is conducted centrally through the Finance and General Administration Division (BAUK), supported by an internal audit system every six months. The primary sources of financing come from student contributions and donations from the foundation, managed with principles of transparency and accountability. Additionally, STIQ As-Syifa integrates formal learning programs with Al-Qur'an memorization, which affects the cost structure and financing model applied. However, the main challenges include budget limitations, minimal government assistance, and low participation from the private sector in funding. To address these constraints, STIQ As-Syifa needs to develop innovative strategies in fund management, such as diversifying funding sources and optimizing community participation.